2014
DOI: 10.1016/j.cplett.2013.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Rate constant of the reaction between CH3O2 and OH radicals

Abstract: The rate constant of the reaction OH + CH 3 O 2 → products (R1). has been measured at 294K by simultaneous coupling of Laser Induced Fluorescence (LIF) and cw-Cavity Ring Down Spectroscopy (cw-CDRS) to laser photolysis. OH radicals were generated by 248nm photolysis of either O 3 in the presence of H 2 O or H 2 O 2 , CH 3 O 2 radicalswere generated simultaneously by photolysis of CH 3 I and their absolute concentrations were obtained by cw-CRDS. OH decays were measured under excess CH 3 O 2 concentrations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
119
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(129 citation statements)
references
References 41 publications
4
119
6
Order By: Relevance
“…Reported experimental values for the rate constant of the reaction of the simplest peroxy radical, CH3O2, with OH disagree by more than a factor of 3. The highest value to date, reported by Bossolasco et al (2014) (2.8 × 10 −10 cm 3 molecule…”
Section: Overall Contribution Of Modelled Ro2 To Kohmentioning
confidence: 97%
See 3 more Smart Citations
“…Reported experimental values for the rate constant of the reaction of the simplest peroxy radical, CH3O2, with OH disagree by more than a factor of 3. The highest value to date, reported by Bossolasco et al (2014) (2.8 × 10 −10 cm 3 molecule…”
Section: Overall Contribution Of Modelled Ro2 To Kohmentioning
confidence: 97%
“…A theoretical study identified R4c as a potentially significant source of methanol in the remote boundary layer and modelled its impacts (Müller et al, 2016). However this study predated the first (and, so far, only) experimental determination of the products of R4, and also used the very high value of k4 reported by Bossolasco et al (2014), which has since been revised to a value almost a factor of 2 lower than the original (as discussed in Section 5.1).…”
Section: The Ch3o2 + Oh Reaction and Product Branching Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, low terpene and NO regimes, prevailing during CYPHEX, and the absence of limonene chemistry in the current model scheme, precluded a more rigorous analysis of the probable chemical pathways for RO2 degradation in the atmosphere. Further, there is evidence that the rate constant of CH3O2 with OH could be two times faster than used in the 30 current models (Bossolasco et al, 2014). Applying this in general to other peroxides, the rate constants need to be revisited as they will have a non-negligible impact on the chemical composition of the atmosphere, especially in remote low NOx environments where the peroxide lifetimes are relatively long.…”
Section: Discussionmentioning
confidence: 99%